Politics in the Human Interest: Applying Sociology in the Real World - Bois, William; Wright, Dean R. (Lexington Books, 2007)
Politics in the Human Interest presents the striking proposition that by paying attention to what's been learned about human behavior, we can develop a political agenda that is in the human interest. Du Bois and Wright, editors of Applying Sociology: Making a Better World, seek a synthesis of the disciplines by returning to the bold conversation of August Comte, Lester Ward, Robert Lynd, Erich Fromm, Abraham Maslow, Alvin Gouldner, Ernest Becker and Alfred McClung Lee. As economist Kenneth Boulding once said, 'The question for the social sciences is simply, what is better_and how do we get there?' Politics in the Human Interest provides an important foundation for the answer and explores the theoretical foundation of a humanistic sociology. It returns to the original progressive agenda_that knowledge about human behavior can be used to create social progress and a better world. Politics in the Human Interest is perfect for advanced undergraduate courses and graduate courses as well as sociology professionals.